Internalisasi Nilai-nilai Pendidikan Islam pada Remaja di Lingkungan Eks Lokalisasi - Ahya Alfiyan Nur; Wulandari Wulandari; Noor Malihah; Ferli Septi Irwansyah; Muchammad Eka Mahmud (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study analyzes the process of internalizing Islamic educational values among adolescents living in the former prostitution area of KM 10 Loa Janan, East Kalimantan, as well as the supporting and inhibiting factors involved. A qualitative approach with a phenomenological method was employed. Data were collected through observation, semi-structured interviews, and documentation with purposively selected parents, religious leaders, community leaders, and adolescents. Data were analyzed through data condensation, data display, and conclusion drawing, while data credibility was ensured through source and technique triangulation. The findings reveal that the internalization of Islamic educational values occurs in three stages: value transformation through role modeling; value transaction through habituation and participation in religious activities; and transinternalization through discipline and counseling. The process is supported by the continuity of religious activities within the community and the collaboration among parents, religious leaders, and community leaders. Conversely, external social influences surrounding the former prostitution area and uncontrolled use of digital devices constitute major obstacles. The study demonstrates that a socially vulnerable environment does not necessarily hinder the development of adolescents’ religious character when supported by sustained religious guidance and community engagement. These findings contribute to a broader understanding of Islamic value internalization in complex social settings